A comparative evaluation of the efficacy of different mandibular anesthetic techniques in patients with irreversible pulpitis - Rini Sharma; T Jayakumar; S Lekha; A Srirekha; Srinivas Panchajanya; R S Shwetha; Kamal Odedra (Wolters Kluwer Medknow Publications, 2018)
Aim: To determine the most efficacious anaesthetic technique in irreversible pulpitis by comparing the anaesthetic efficacies of Gow-Gates, Vazirani-Akinosi, Inferior alveolar nerve block with buccal infiltration and conventional Inferior alveolar nerve block (IANB) using 2% Lidocaine with 1:80,000 epinephrine as the anaesthetic agent in mandibular first molars. Methodology: 120 patients with inflamed vital pulp and lingering pain on removal of the stimulus were randomly divided into 4 groups in which the local anaesthetic was administered by the different techniques. Group I (n = 30) Gow-Gates technique. Group II (n = 30) Vazirani-Akinosi technique. Group III (n = 30) IANB with buccal infiltration. Group IV (n = 30) Conventional IANB. Anaesthesia was considered effective when ''no pain'' or "mild pain" felt by the patient during access preparation. Results: The Statistical software used were SAS 9.2, SPSS 15.0, Stata 10.1, MedCalc 9.0.1, Systat 12.0 and R environment ver.2.11.1. The results demonstrated that the Gow-Gates technique showed greater anaesthetic success (66.7%) followed by Vazirani Akinosi technique (60%) as compared to the conventional IANB. There was however no statistical significance observed between the groups. Conclusion: Gow Gates mandibular conduction block may increase the anaesthetic success rates in cases of irreversible pulpitis in mandibular molars as compared to other techniques.